2020
DOI: 10.1007/s10452-020-09768-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multigenerational rearing, ontogeny and predation threat on copepod feeding rhythms

Abstract: Marine planktonic copepods frequently exhibit diel feeding cycles coupled with vertical migrations. However, copepod feeding rhythms can be influenced by factors others than different food availability between layers. In this study we determined the changes in the diel feeding behaviour of two marine copepod species (Centropages typicus and Paracartia grani) through multigenerational laboratory rearing, ontogeny, and upon the exposure to predator chemical cues. The wild females of both C. typicus and P. grani … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…One could expect that copepods’ ability to respond to predator cues would be reduced or lost after >65 generations in culture. Culture conditions with ample food select for continuous feeding and fast growth, and thereby against behaviors that reduce growth, such as diel feeding cycles (Tiselius et al 1995, Olivares et al 2020) and potentially predator avoidance. Moreover, the culture population likely differs from wild populations due to founder effects, genetic drift and inbreeding, which typically result in loss of genetic variation (Futuyma 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One could expect that copepods’ ability to respond to predator cues would be reduced or lost after >65 generations in culture. Culture conditions with ample food select for continuous feeding and fast growth, and thereby against behaviors that reduce growth, such as diel feeding cycles (Tiselius et al 1995, Olivares et al 2020) and potentially predator avoidance. Moreover, the culture population likely differs from wild populations due to founder effects, genetic drift and inbreeding, which typically result in loss of genetic variation (Futuyma 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the other protists studied also seemed to show a time-dependent weakening of their diel feeding rhythm, although at a much longer scale (years). The fading of a diel feeding rhythm in the absence of predators in the laboratory has already been documented for marine copepods [27], and the presence of fish has also been reported to sharply enhance their diel feeding cycle [28], although the role of chemical cues alone might not be so clear [29,30]. However, the physical presence of fish can induce changes in some behavioural and morphological traits of copepods.…”
Section: (A) Loss and Recovery Of The Feeding Rhythms In The Laboratory: The Particular Case Of Ciliatesmentioning
confidence: 99%
“…It is reported that a variety of birds in the world constantly migrate from one place to another every year. They can migrate over vast geographical areas and cross biological and geographical boundaries ( 7 ). Birds can act as a source of infections for public health and animals through direct contact or as carriers of pathogens including avian and zoonotic pathogens and antibiotic-resistant bacteria ( 8 ).…”
Section: Introductionmentioning
confidence: 99%